Healthy Selfishness and Pathological Altruism: Measuring Two Paradoxical Forms of Selfishness - Kaufman, Scott Barry; Jauk, Emanuel (Frontiers in Psychology, 2020)
Selfishness is often regarded as an undesirable or even immoral characteristic, whereas altruism is typically considered universally desirable and virtuous. However, human history as well as the works of humanistic and psychodynamic psychologists point to a more complex picture, highlighting the fact that not all selfishness is necessarily bad, and not all altruism is necessarily good. Based on these writings, we introduce new scales for the assessment of two paradoxical forms of selfishness that have lacked measurement in the field – healthy selfishness (HS) and pathological altruism (PA). In two studies (N1 = 370, N2 = 891), we constructed and validated the HS and PA scales. The scales showed good internal consistency and a clear two-dimensional structure across both studies. HS was related to higher levels of psychological well-being and adaptive psychological functioning as well as a genuine prosocial orientation. PA was associated with maladaptive psychological outcomes, vulnerable narcissism, and selfish motivations for helping others. These results underpin the paradoxical nature of both constructs. We discuss the implications for future research, including clinical implications.